The Influence of Public Perception and Implementation of the MBG Program on the Image of Prabowo–Gibran Government - Yarnis Yarnis; Astriana Baiti Sinaga; Nani Nurani Muksin; Tria Patrianti (Lentera: Jurnal Ilmu Dakwah dan Komunikasi, 2026)
This study measures the influence of public perception and the Free Nutritious Meals Program (MBG) on the image of the Prabowo–Gibran administration in Berau Regency. In political communication, the MBG program is viewed not only in terms of its implementation but also in how it is perceived by the public and communicated by the government. This study is motivated by the existence of both pros and cons regarding the new leadership and the challenges faced by the new government's image, particularly in programs that have not yet been fully realized, especially in areas such as Berau Regency, which is geographically quite distant from the centre of government. The objective of this study is to measure the influence of public perception and the implementation of the MBG program on the government's image. The method used is quantitative, with a survey method. The sample consists of 100 respondents selected through stratified random sampling in Berau Regency. The results indicate that public perception does not have a significant influence on the government's image. Conversely, the MBG program partially has a strong influence. However, when tested simultaneously, both contribute significantly to forming a positive image of the government. These findings indicate that narratives and strategic communication regarding programs that have not yet been fully implemented can still influence the government's image. In Political PR, these results highlight the importance of effective political communication and make theoretical and practical contributions to the development of political communication strategies.